Platelet-rich plasma as a chance of recovery for liver cirrhosis patient - O. L. Appelhans; M. M. Perepeliuk; O. I. Romak; L. A. Polukarova (Kazimierz Wielki University, 2019)
The search for pathogenetic methods for treating cirrhosis of the liver continues. One of the promising areas of regenerative medicine is the use of platelet-rich plasma (PRP). Due to numerous publications on the efficacy of PRP in conditions of abnormal liver damage in the experiment, the work is devoted to the study of the possibility of manufacturing PRP from the blood of patients with liver cirrhosis (LC) for the purpose of proposals for further clinical use. The study included 12 men suffering from CP-class B-C (average grade by Child-Pugh classification - 8.8) at the age of 45 ± 2.2 years. The comparison group consisted of 5 healthy men at the age of 44 ± 1.8 years. All men measured blood platelets in accordance with the usual method. The manufacture of PRP was carried out according to the scheme, which includes the collection of blood from the elbow vein in a 9 ml syringe-flask, which contains an anticoagulant. The collected blood in the same test tube is centrifuged in two stages: on the first - within 12` at a speed of 4000 rpm. Then the formed plasma, namely, from the supernatant layer, is recruited into another tube without an anticoagulant and treated in a centrifuge for 15` at a speed of 3600 rpm. After the removal of poor plasma platelets, the final product - a PRP aggregate in the volume of 0.3 ml - is obtained, which is used for the next determination of platelet count using an automated hemo-analyzer. In patients with LC, both thrombocytopenia and thrombocytosis were observed. In the PRP, the increase in the total platelet count was 2.2-2.4 times, both in baseline thrombocytopenia and in baseline thrombocytosis, due to the absence of the mean platelet count and the platelet distribution width. In the control group male, the average increase in the number of platelets was 3.37 times, in the absence of significant changes in the mean platelet count and platelet distribution width. The fact is that the use of autologous PRP in patients with LC is likely to be ineffective. In the presence of initial thrombocytopenia - there is no possibility to reach a "critical" quantity of 1 million G/L, which is necessary for the implementation of regenerative potential of PRP. Concomitant presence of morpho-functional defects of these platelets practically makes it impossible for such a method of protection/regeneration of liver parenchyma in patients with lC. In patients with LC there is a moderate increase in the concentration of platelets in the manufacture of PRP by standard method; therefore, it is necessary to find new methods for obtaining PRP for autologous use.